Widows at the Hustings: Gender, Citizenship, and the Montreal By-Election of 1832 - Bradbury, Bettina (Women on their Own. Interdisciplinary Perspectives on Being Single, 2008)
Keywords: Femmes; Élections

Le Devoir et le groupe des conservateurs-nationalistes après les élections fédérales du 21 septembre 1911 - Moreau, Aurélie (Université d'Angers, 2002)
Keywords: Devoir (Le); Nationalisme; Élections

Le Front d’action politique (FRAP) à Montréal: de la naissance aux élections (1969-1970) - Comby, Marc (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2001)
Number: 2
Keywords: Groupes populaires; Partis politiques; Élections

Divided by the Ballot Box: The Montreal Council of Women and the 1917 Election - Brookfield, Tarah (Canadian Historical Review, 2008)
Number: 4
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Élections

Les élections scolaires au Québec à travers les sondages d’opinion - Proulx, Jean-Pierre (Recherches sociographiques, 2008)
Number: 2

La politique municipale à Montréal dans les années 1990: du ''réformisme populaire'' au ''populisme gestionnaire'' - Belley, Serge (Politique et Sociétés, 2003)
Number: 1
Keywords: Élections

Pierre Bédard: le devoir et la justice: 1re partie – La liberté du Parlement et de la presse - Gallichan, Gilles (Les Cahiers des Dix, 2009)
Number: 63
Keywords: Députés; Élections

L'influence de la localisation géographique et des caractéristiques socio-économiques des quartiers de la MRM de Montréal dans le processus de la participation électorale - Carrier, Mathieu (Université Laval, 2007)
Keywords: Quartiers; Élections

L’historiographie récente sur Wilfrid Laurier - Nichols, Jean-Mathieu (Université du Québec à Montréal, 2006)
Keywords: Histoire; Libéralisme; Élections

Camillien Houde. Maire de Montréal, quelques jalons - Dupont, Antonin (Il était une fois... Montréal-Nord, 2005)
issued: 2005-23-00
Keywords: Houde; Camillien; Maires; Élections

Le 21 mai 1832, sur la Rue du Sang - Boileau, Gilles (Histoire Québec, 2001)
Number: 3
Keywords: Bagg; Stanley; Tracey; Daniel; Élections; Émeutes

L'implication sociale et politique de Jacques Couture à Montréal de 1963 à 1976 - Croteau, Martin (Université du Québec à Montréal, 2008)
Keywords: Communautés religieuses; Groupes populaires; Jésuites; Pauvreté; Quartiers; Élections

Mouvements sociaux, syndicats et action politique à Montréal: l'histoire du FRAP (1970-1974) - Comby, Marc (Université de Montréal, 2005)
Keywords: Crise d'octobre; Drapeau; Jean; Groupes populaires; Partis politiques; Élections

L'expérience du FRAP à Montréal (1970-1974). La tentative de créer au Québec un parti d'extrême gauche - Comby, Marc (Contester dans un pays prospère: l'extrême gauche en Belgique et au Canada, 2007)
Keywords: Crise d'octobre; Drapeau; Jean; Groupes populaires; Partis politiques; Élections

From Bourassa to Bourassa: Wilderness to Restoration - MacDonald, L. Ian (McGill-Queen's University Press, 2002)
"From Bourassa to Bourassa is a narrative history of the Quebec Liberal Party during its wilderness years after the 1976 election of the Parti Quebecois and its subsequent restoration in 1985." "First published to critical acclaim in 1984, From Bourassa to Bourassa, 2nd edition, updates the story with Bourassa's landslide election victory in 1985 and his subsequent role in the Meech Lake Accord and the Canada-U.S. Free Trade Agreement, the two issues that largely defined the decade of the 1980s for Quebec and for Canada."–BOOK JACKET.
Keywords: Bourassa; Robert; Partis politiques